2007
DOI: 10.1177/003335490712200610
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Exposure to Chlorine Released from a Train Derailment and Resulting Health Impact

Abstract: The rapid investigation revealed significant morbidity and mortality associated with an accidental release of chlorine gas. Key findings that should be addressed during facility, community, state, and regional mass-casualty planning include self-transport of symptomatic people for medical care and impact on health-care facilities over a wide geographic area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 1 publication
3
71
0
Order By: Relevance
“…Besides pulmonary edema and respiratory failure, more than 90% of fatalities due to acute high-level chlorine exposure may be due to cardiovascular complications (1,(22)(23)(24). Our earlier studies with environmental oxidant gas exposures revealed enhanced airway epithelial cell death and subsequent loss of SERCA activity (17,25).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Besides pulmonary edema and respiratory failure, more than 90% of fatalities due to acute high-level chlorine exposure may be due to cardiovascular complications (1,(22)(23)(24). Our earlier studies with environmental oxidant gas exposures revealed enhanced airway epithelial cell death and subsequent loss of SERCA activity (17,25).…”
Section: Discussionmentioning
confidence: 91%
“…These studies proposed a role for particulate matter-induced cardiovascular inflammation and oxidative stress (29). Cardiac effects of chlorine, especially cardiomegaly, were reported in autopsies of human victims of acute high-concentration chlorine gas exposure (1,(22)(23)(24). Similarly, experimental dogs that died of acute chlorine exposure had dilated right ventricles (30).…”
Section: Discussionmentioning
confidence: 99%
“…We believed that employee annual spirometry assessments could be used to assess community lung health before and after the train accident. Mill buildings were located in close proximity to the crash site, and nearly 200 employees were working at the time of the accident (4). Moreover, the accident occurred at 02:40 hours, and many mill worker residents were exposed to chlorine while sleeping in their nearby homes.…”
mentioning
confidence: 99%
“…Cl 2 gas exposure is a documented public health threat mainly because of accidents involved in its trafficking and deliberate release involved in warfare; therefore increased preparedness is required to avoid mass casualty situations (26,51,55,56). Apart from the fact that significant morbidity and mortality are entailed in cases of acute exposure, there are also long-term residual clinical symptoms, such as reactive airway disease syndrome, reduced residual volume, and reduced forced vital capacity (4,12,16,45).…”
Section: Discussionmentioning
confidence: 99%